Review of Best Teaching Methodologies in Rural Areas - Sumathi, A; Nithyashankari, P (International Journal of Computer Sciences and Engineering, 2020)
This paper extracts and broadens rural teachers’ most effective proclaimed motivating strategies. From the data generated by 2 years of mixed method research in rural college, these strategies appeared as among the most victorious. Selection of best practices was formed on a synthesis of what both teachers and students reported as making the greatest positive impact on their colleges’ related motivation. Teaching strategies are illustrated by multiple exhaustive examples from teachers’ interviews. Strategies are i) start with your classroom set up, ii) make digital citizenship a priority, iii) teach minilessons before using devices, iv) use the power of choice, v) remember that sharing is caring, vi) conduct teacher check-ins etc. The teaching methodology is surveyed through the college. The surveyed data is plotted using histogram graph method using MATLAB platform. Histogram is a graphical display of data using bars of different heights. It is similar to a bar chart, but a histogram group’s number into ranges. The height of each bar shows how many fall into each range.